2014
DOI: 10.1016/j.jgr.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside profiles and related gene expression during foliation in Panax ginseng Meyer

Abstract: Panax ginseng is one of the most important medicinal plants in Asia. Triterpene saponins, known as ginsenosides, are the major pharmacological compounds in P. ginseng. The present study was conducted to evaluate the changes in ginsenoside composition according to the foliation stage of P. ginseng cultured in a hydroponic system. Among the three tested growth stages (closed, intermediate, and opened), the highest amount of total ginsenoside in the main and fine roots was in the intermediate stage. In the leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 31 publications
(25 reference statements)
3
63
1
Order By: Relevance
“…Moreover, Rb2, Rb3, and Rg1 were only detected in the root hair, leaf, and main root, respectively. Kim et al (21) suggested that the difference of ginsenosides in the parts of Panax ginseng may be due to the movement of ginsenosides between the roots, shoots, and leaves during foliation. Although there have not been any studies investigating the movement of ginsenosides in ginseng, there is evidence for this phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Rb2, Rb3, and Rg1 were only detected in the root hair, leaf, and main root, respectively. Kim et al (21) suggested that the difference of ginsenosides in the parts of Panax ginseng may be due to the movement of ginsenosides between the roots, shoots, and leaves during foliation. Although there have not been any studies investigating the movement of ginsenosides in ginseng, there is evidence for this phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…1). In addition, during the foliation of leaves from previous year roots, ginsenoside content of leaves become markedly increased, conversely, those in the roots decrease (Kim et al, 2014a), suggesting the dynamic movement or synthesis during each year of growth. Even though investigations have been performed to understand the mechanism of ginsenoside synthesis and distribution, the long-distance allocation of ginsenosides remains largely unknown.…”
Section: Dynamics Of Ginsenoside Accumulation and The Physiological Fmentioning
confidence: 98%
“…At the initial stage, the aerial parts exhibit a parasol-like shape ( Fig. 1a(i), b(i); Kim et al 2014), showing unfolded leaves attached to the bending stem, and an inflorescence primordia attached to a short peduncle ( Fig. 1c(i)).…”
Section: Inflorescence Developmentmentioning
confidence: 99%